Characterization of the koch fractal hexagonal loop frequency selective surface for X-band application - Nur Biha Binti Mohamed Nafis; Mohamad Kamal Bin A. Rahim; Osman Bin Ayop; Huda Bin A MAjid; Sunti Tuntrakool (Institute of Advanced Engineering and Science, 2020)
This paper presented the bandstop Koch fractal hexagonal loop frequency selective surface (FSS) for the X-band application. The simulated transmission coefficient response (S_21) had been obtained by using CST software. The proposed Koch fractal hexagonal loop FSS structure is highly insensitive towards angular stability and also incident polarization up to 60 degree , with deviation of resonant frequency, f_r below than 1%. The parametric analysis on the effect of the periodicity, width, and height of the fractal FSS structure on the S_21 has been illustrated and discussed thoroughly.